Optimization of γ-Aminobutyric Acid (GABA) Accumulation in Germinating Adzuki Beans (Vigna angularis) by Vacuum Treatment and Monosodium Glutamate, and the Molecular Mechanisms - Jiang, Xiujie; Xu, Qingpeng; Zhang, Aiwu; Liu, Yong; Zhao, Liqin; Gu, Liwei; Yuan, Jianbin; Jia, Hongdou; Shen, Xinting; Li, Zhijiang; Cao, Dongmei; Zhang, Dongjie (Frontiers in Nutrition, 2021)
This study aimed to investigate the optimal hypoxic and monosodium glutamate (MSG) stress conditions for the enrichment of γ-Aminobutyric acid (GABA) in germinating adzuki beans and to reveal the potential underlying molecular mechanisms of GABA accumulation. Using single-factor experiments and response surface model, we investigated the effects of germination time, germination temperature, vacuum time, and MSG concentration on GABA contents, and further explored the activity and gene expression of glutamate decarboxylase (GAD) and polyamine oxidase (PAO) critical rate restriction enzymes during GABA synthesis. The optimal soaking temperature, soaking time, and pH conditions were 35°C, 16 h, and 5, respectively. Furthermore, the optimal germination conditions for optimal GABA enrichment were 48 h, 1.99 mg/ml MSG concentration, germination temperature of 31.49°C, and vacuum time of 15.83 h. Under such conditions, the predicted GABA concentration was 443.57 ± 7.18 mg/100 g, with no significant difference between the predicted and experimental data. The vacuum + MSG (FZM) treatment has a maximum contribution rate of GABA to 38.29%, which significantly increase GABA content, and the increase was associated with increased GAD and PAO activity. In addition, MSG in combination with vacuum treatment could significantly induce VaGAD4 and VaGAD6 genes in 2 days germination of adzuki beans. According to the results of the present study, vacuum + MSG treatment is an effective approach to enhancing GABA accumulation in germinating adzuki beans, which could be employed in enhancing the functional quality of germinating adzuki beans.